Coniochaetidium Zulianensis, A New Record In The World - Delgado ívilaAdolfredo E.; Urdaneta García, Lilia M.; Piñeiro Chávez, Albino J. (Revista Científica de la Facultad de Ciencias Veterinarias)
<!–[if gte mso 9]> Normal 0 21 false false false MicrosoftInternetExplorer4 <![endif]–><!–[if gte mso 9]> <![endif]–><!–[if !mso]> <![endif]–> <!– /* Font Definitions */ @font-face font-family:Verdana; panose-1:2 11 6 4 3 5 4 4 2 4; mso-font-charset:0; mso-generic-font-family:swiss; mso-font-pitch:variable; mso-font-signature:536871559 0 0 0 415 0; /* Style Definitions */ p.MsoNormal, li.MsoNormal, div.MsoNormal mso-style-parent:""; margin:0cm; margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:12.0pt; font-family:"Times New Roman"; mso-fareast-font-family:"Times New Roman"; @page Section1 size:612.0pt 792.0pt; margin:70.85pt 3.0cm 70.85pt 3.0cm; mso-header-margin:36.0pt; mso-footer-margin:36.0pt; mso-paper-source:0; div.Section1 page:Section1; –> <!–[if gte mso 10]> <![endif]–>On the basis of a study of coprophilous fungi from Zulia state, Venezuela, one specie of the family Coniochaetaceae, with cleistothecial ascocarp and ascospores with germ pore was isolated from dove dung. It was identified as species of Coniochaetidium Malloch and Cain. The species described in this paper differs from the other five (5) species in its morphological characteristic, globose asci, 8 spored and ellipsoidal ascospores, also this species differs from another by having larger ascopores, which are nearly double its length in culture. The species was identified as Coniochaetidium zulianensis Delgado, Urdaneta and Piñeiro, which represents a new record in the world